Reduksi Ion Cu(II) Menggunakan Karbon Aktif dari Sekam Padi Teraktivasi Fisika dan Kimia - Eka Purnawan; Abrar Muslim; Nasrullah Razali; Muhammad Zaki; Hesti Meilina; Azwar Azwar (Fakultas Teknik, 2020)
This research proposed a method to produce activated carbon from rice husk by carbonation process, physical activation and chemical activation using NaOH. The performance of activated carbon was tested by batch experiments in which the adsorption system contained 1 g of rice husk activated carbon in 100 mL of artificial wastewater with initial concentration of Cu(II) ion being 148.26 mg/L, initial pH 6, at 27 oC and 1 atm to determine the efficiency of reducing Cu(II) ion over the contact time and presence of stirring on chemical activation. The results showed that the efficiency of reducing Cu(II) ion by rice husk activated carbon increased exponentially with increasing contact time with a maximum value of 74.33% at 90 minutes of contact time. The results also showed that stirring on chemical activation increased the efficiency of Cu(II) ion reduction by 14.94%. Adsorption kinetics studies showed that Cu(II) ion reduction followed the pseudo-second order adsorption equation with the adsorption capacity of 10.18 mg/g and adsorption rate constant of 0.0013 g/mg.min for rice husk activated carbon without stirring in the chemical activation. Stirring in the chemical activation.increased the capacity and rate of adsorption constant to 12.07 mg/g and 0.0052 g/mg.min, respectively.